Antibacterial Activity of Endophytic Fungi from Elephant Ginger Rhizome (Zingiber officinale var. Roscoe) Against Methicillin Resistant Staphylococcus aureus (MRSA) - Sari, Ni Ketut Yuliana; Kawuri, Retno; Parwanayoni, Ni Made Susun (Metamorfosa: Journal of Biological Sciences, 2020)
This study aimed to isolate and test the antibacterial activity of endophytic fungi from elephant ginger rhizome ( Zingiber officinale var. Roscoe) against MRSA. This research is an exploratory research which is continued with experimental. The research sample was obtained from three locations. The first sample was from Pancasari Village, Singaraja, Bali. The second sample was from Peguyanganan Village, Denpasar, Bali. The third sample is from Tebuana Village, Tampaksiring, Bali. This research was conducted at the Microbiology Laboratory, Department of Biology, Faculty of Mathematics and Natural Sciences, Udayana University. Eight isolates of endophytic fungi were successfully isolated with each inhibitory zone against MRSA, Fusarium sp. 1 (21 mm), Fusarium sp. 2 (19 mm), Fusarium sp. 3 (20 mm), Fusarium sp. 4 (21 mm), Aspergillus sp. 1 (32 mm), Aspergillus sp. 2 (25 mm), Fungi S3F1 (13 mm) and Fusarium sp. 5 (25 mm). This shows that endophytic fungi can be used as an alternative producer of antibacterial compounds.   Keywords: Antibacterial, Endophytic fungi, Methicillin Resistant Staphylococcus aureus .